Operasi Motor Induksi Tiga Fasa Pada Sistem Satu Fasa - Petrus Setyo Prabowo; Second Adrian Christianto (Media Teknika, 2017)
At this time the 3-phase induction motors are needed in many areas including small industries and in areas having only 1-phase electrical system. The area requires a motor with a large driving force that can be operated with both normal and 1-phase electrical system. An induction motor can work ineither normal configuration or modified configuration with adding a series of capacitor motors in 3-phase induction motor. The series capacitors are used with an auxiliary coil is placed on the side or sides of the coil which has a larger impedance. In this study, the performance of 3-phase induction motors is supported with 1-phase electrical system coupled with the ACS758 current sensor . This coupling is to measure the current value of the load being used. When the ACS758 current sensor detects the passing current, it will display the current value on the LCD which facilitates the user in the current value of the measured reading. Induction motor can work well and normal with 1-phase electrical system using a series of capacitor motors. Measurement with current sensor has an error less than 2%.Keywords: 3-phase induction motor, 1-phase electrical system, LCD